Autologous Homologous Skin Constructs Allow Safe Closure of Wounds: A Retrospective, Noncontrolled, Multicentered Case Series. Issue 5 (May 2020) - Mundinger, Gerhard S.; Armstrong, David G.; Smith, David J.; Sailon, Alexander M.; Chatterjee, Abhishek; Tamagnini, Greg; Partridge, Joanna; Baetz, Nicholas; Labroo, Pratima; Swanson, Edward W.; Sopko, Nikolai A.; Granick, Mark S.
Abstract : Summary: An autologous homologous skin construct (AHSC) has been developed for the repair and replacement of skin. It is created from a small, full-thickness harvest of healthy skin, which contains endogenous regenerative populations involved in native skin repair. A multicenter retrospective review of 15 wounds in 15 patients treated with AHSC was performed to evaluate the hypothesis that a single application could result in wound closure in a variety of wound types and that the resulting tissue would resemble native skin. Patients and wounds were selected and managed per provider's discretion with no predefined inclusion, exclusion, or follow-up criteria. Dressings were changed weekly. Graft take and wound closure were documented during follow-up visits and imaged with a digital camera. Wound etiologies included 5 acute and chronic burn, 4 acute traumatic, and 6 chronic wounds. All wounds were closed with a single application of AHSC manufactured from a single tissue harvest. Median wound, harvest, and defect-to-harvest size ratio were 120 cm 2 (range, 27–4800 cm 2 ), 14 cm 2 (range, 3–20 cm 2 ), and 11:1 (range, 2:1–343:1), respectively. No adverse reactions with the full-thickness harvest site or the AHSC treatment site were reported. Average follow-up was 4 ± 3 months. An AHSC-treated area was biopsied, and a micrograph of the area was developed using immunofluorescent confocal microscopy, which demonstrated mature, full-thickness skin with nascent hair follicles and glands. This early clinical experience with ASHC suggests that it can close different wound types; however, additional studies are needed to verify this statement. Abstract : Supplemental Digital Content is available in the text.